1989
DOI: 10.1103/physrevb.39.10373
|View full text |Cite
|
Sign up to set email alerts
|

Secular equation of Korringa, Kohn, and Rostoker for the case of non-muffin-tin, space-filling potential cells

Abstract: Proof is provided that the secular equation proposed by Korringa, Kohn, and Rostoker for determining the electronic structure of collections of mufFin-tin potentials, i.e. , potentials bounded by nonoverlapping spheres, remains valid in the completely general case of nonoverlapping, arbitrarily shaped, and particularly space-filling potential cells. Consequently, this secular equation leads to the proper coefBcients for determining the wave function of the system as a linear combination of cell wave functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Define s, = Ron + t,,, n f 0, (26) sg = max(s1,s2 ,..., sN). (27) and let s o be a maximum value among s,: The value so corresponds to the radius of a sphere, circumscribing all the "molecule." Introduce a sphere '3Jbo, centered at the origin ( R o = 0) and having a radius po such as po > so.…”
Section: (Rml D P)mentioning
confidence: 99%
See 1 more Smart Citation
“…Define s, = Ron + t,,, n f 0, (26) sg = max(s1,s2 ,..., sN). (27) and let s o be a maximum value among s,: The value so corresponds to the radius of a sphere, circumscribing all the "molecule." Introduce a sphere '3Jbo, centered at the origin ( R o = 0) and having a radius po such as po > so.…”
Section: (Rml D P)mentioning
confidence: 99%
“…Additionally, Keister [lo] has demonstrated that, in practice, the divergent series may not lead to some troubles, because of their asymptotic, semiconvergent nature. On the other hand, Gonis et al [13,24], Zhang et al [27,28], and Molenaar [19] have given reasons for the difficulties with the summations of divergent series virtually not to exist. To draw such a conclusion, they put forward a procedure by which the origins of cells should be shifted.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recently a great deal of work has been directed at the generalization of the KKR method to space-filling cells. Much of this work has established [25][26][27][28][29][30][31][32] that, as far as the band structure of a material is concerned, multiple-scattering theory (MST) assumes identical forms in both the case of MT and the case of space-filling cells. In fact, in all its manifestations, MST retains one of its most advantageous features, namely the separability of the structural aspects from the potential aspects of a scattering assembly.…”
Section: Introductionmentioning
confidence: 99%